OPINI AUDIT ONGOING CONCERN DAN ANALISA LAPORAN KEUANGAN SEBAGAI PENENTU KEBERLANGSUNGAN HIDUP PERUSAHAAN - BARUS UMARELLA (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2019)
Provision of going concern audit opinion is the auditor's responsibility in addition to examining the auditee's financial statements. Failure to give an audit opinion will greatly affect the company's sustainability. This research tries to dig deeper into the phenomenon of giving a going-concern audit opinion that serves as a benchmark for investment and an overview of the company's financial condition based on an analysis of financial statements. This research is a qualitative study that analyzes and explains research issues based on secondary data, namely the company's annual financial statements and independent audit reports and the results of searches with related parties. The results showed that going concern audit opinion greatly affects the company's investment in the future because the opinion is a benchmark for auditors in assessing the company's financial condition which has a direct impact on the company's survival.